2022
DOI: 10.3389/fpsyg.2022.930857
|View full text |Cite
|
Sign up to set email alerts
|

Intergenerational relationship quality, sense of loneliness, and attitude toward later life among aging Chinese adults in Hong Kong

Abstract: A positive attitude toward later life is crucial for wellbeing among older adults. Maintaining a healthy relationship with adult children can help reduce older parents’ sense of loneliness and nurture a positive life attitude. This study aimed to investigate the associations between multidimensional intergenerational relationship quality and attitudes toward later life among aging Chinese adults in Hong Kong and examine the mediating effects of a sense of loneliness. Representative survey data were collected f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Cognitive programs while implimentating active aging strategy for those isolated older adults should be emphasized. For instance, by fostering an age-friendly environment and acknowledging the role of older adults, Chinese society might reduce negative attitudes toward aging, At the same time, the social participation of older adults can be encouraged to enhance positive self-identity, and improving the quality of intergenerational relations has also been found to be an effective way to improve the positive aging attitude of older Chinese ( Liu et al, 2022 ). Second, for family members and social workers of older adults, future intervention and treatment programs for loneliness may include assessing and measuring aging attitudes.…”
Section: Discussionmentioning
confidence: 99%
“…Cognitive programs while implimentating active aging strategy for those isolated older adults should be emphasized. For instance, by fostering an age-friendly environment and acknowledging the role of older adults, Chinese society might reduce negative attitudes toward aging, At the same time, the social participation of older adults can be encouraged to enhance positive self-identity, and improving the quality of intergenerational relations has also been found to be an effective way to improve the positive aging attitude of older Chinese ( Liu et al, 2022 ). Second, for family members and social workers of older adults, future intervention and treatment programs for loneliness may include assessing and measuring aging attitudes.…”
Section: Discussionmentioning
confidence: 99%
“…25,27 Research evidences of different paradigms showed that intergroup contact may positively relieve loneliness, as both longitudinal and horizontal studies have proved the positive effects of intergroup contact on individual problem-solving, cognitive flexibility, creativity, well-being and mental health in multiple groups, including cross-hukou-regional, ethnic, gender and country. 26,[28][29][30][31][32][33][34][35][36] Specifically, an intergenerational technology program brings disparate age groups together to interact in meaningful activities, resulting in effectively reducing loneliness for older adults. 29 Our hypothesis thus is that intergroup contact may alleviate loneliness.…”
Section: Lonelinessmentioning
confidence: 99%